2015
DOI: 10.1136/annrheumdis-2014-207202
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of the squeeze test to identify arthritis: a cross-sectional cohort study

Abstract: A positive squeeze test is associated with local joint inflammation but the sensitivity is low, indicating a high percentage of swollen joints with a negative squeeze test. When the test is used on its own, it is insufficient to detect early arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…We read with deep interest the article by van den Bosch et al 1 related to the diagnostic accuracy of the squeeze test to identify arthritis. This cross-sectional cohort study suggested that a positive squeeze test is associated with local joint inflammation with a very low sensitivity, indicating a high percentage of swollen joints with a negative squeeze test.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with deep interest the article by van den Bosch et al 1 related to the diagnostic accuracy of the squeeze test to identify arthritis. This cross-sectional cohort study suggested that a positive squeeze test is associated with local joint inflammation with a very low sensitivity, indicating a high percentage of swollen joints with a negative squeeze test.…”
mentioning
confidence: 99%
“…First, the authors added proximal interphalangeal joints (PIPs) symptoms as positive physical examination, but there lacked the results of squeeze test about PIPs. Second, ‘the squeeze test’ described by the authors in figure 11 isn’t the ‘validated standard squeeze test’ promoted by experts and societies 2–4. The interphalangeal joints of the hands and feet are held by hand and their pain will lead to a false-positive squeeze test.…”
mentioning
confidence: 99%
“…Adding other clinical variables might increase the discriminative ability of the model. Potential examples include the squeeze test of the metacarpophalangeal joints (although the diagnostic accuracy was shown to be only moderate 28 ), information on family history or functional impairments. These items were not routinely collected before December 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for the squeeze test is that compression of the metacarpophalangeal (MCP) joints evokes pain in an individual with active synovitis. We agree that the squeeze test is useful for identifying early arthritis,4 but its sensitivity is limited and it may need to be combined with other screening tests in order to be sufficiently discriminatory 5. Nonetheless, it is cheap, quick and easy to perform and therefore an appropriate test for the GP who suspects a patient may have developed RA.…”
mentioning
confidence: 80%